Selected Papers from the 8th International Conference of Biotechnologies, Present and Perspectives - Oroian, Mircea; Codină, Georgiana Gabriela (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Special Issue reprint presents the latest developments in the food industry field, with a specific focus on the biotechnological processes that take place in various branches of the food industry, which have major implications in determining the overall quality of food products. This Special Issue capitalizes the experience of the authors in the latest advancements and future trends in biotechnologies from the food industry, applied engineering sciences, food product quality, food safety, environment protection, and equipment for the food industry.